Microwave Activated Synthesis of 2-Imidazolin-5-ones Using Phenyl Isothiocyanate as Cyclocondensing Agent - K. TRIPATHY, PRADEEP (Asian Journal of Chemistry, 2010)
The cyclocondensation reaction of N-acetyl and N-benzoylglycines (1a, b) with aromatic aldehydes in the presence of phenyl isothiocyanate as cyclizing agent and pyridine as a catalyst in an open vessel under microwave irradiation in dry media yielded 4-(arylmethylene)-1-phenyl-2-styryl- and 4-(arylmethylene-1,2-diphenyl-2-imidazolin-5-ones (2f and 2a-e, respectively). It is noteworthy that the reaction is completed within 10 min with much better yields. All the steps are carried out in one pot.